2018
DOI: 10.3390/ma11122522
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of the Properties of Ultrafine to Nanocrystalline Grade 2 Titanium Wires

Abstract: This paper describes the mechanical properties and microstructure of commercially pure titanium (Grade 2) processed with Conform severe plastic deformation (SPD) and rotary swaging techniques. This technology enables ultrafine-grained to nanocrystalline wires to be produced in a continuous process. A comprehensive description is given of those properties which should enable straightforward implementation of the material in medical applications. Conform SPD processing has led to a dramatic refinement of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…In reference [39], Palán et al simulated the conditions which prevailed in the C-ECAP machine. The authors results indicated that the temperature, the strain rate, and the velocity distribution were very inhomogeneous in the die.…”
Section: Microstructure: Ebsd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In reference [39], Palán et al simulated the conditions which prevailed in the C-ECAP machine. The authors results indicated that the temperature, the strain rate, and the velocity distribution were very inhomogeneous in the die.…”
Section: Microstructure: Ebsd Resultsmentioning
confidence: 99%
“…Furthermore, as discussed at the end of section 3.2., different conditions prevailed in different parts of the C-ECAP machine. In reference [39] (Figure 2), it was shown that in the corners and the adjacent areas, the strain rate and velocity distribution was practically zero. This may be additional evidence that the real shear plane can be different from the predicted one ( Figure 11).…”
Section: X-ray Texture Measurementsmentioning
confidence: 98%
“…At COMTES FHT, the method has been modified in order to refine the structure during the forming process; and thus Conform SPD ( Figure 1) was developed. This Conform SPD significantly improved the final mechanical properties [10,11,15]. The grain refinement is achieved thanks to the shear deformation and high hydrostatic pressure inside the processing chamber die which was designed based on experiences with the ECAP procedure [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It is essentially equivalent to the CONFORM ECAP method, but it has a narrower channel angle of 90 • , which provides more severe deformation. The main advantage of these methods is that they allow continuous production [9]. The combination of Conform SPD with rotary swaging was also found to be very effective [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The ductility decreases with increasing strength, which worsens workability of the material. Possible solving of this problem is to apply subsequent heat treatment after severe plastic deformation, as it was described for Ti grade 2 [9]. Suitable heat treatment in this case leads to release of internal stresses but does not cause grain coarsening.…”
Section: Introductionmentioning
confidence: 99%